2021
DOI: 10.1155/2021/8854945
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Inflammation of Curcumae Longae Rhizoma 30% EtOH Extract on Acute Reflux Esophagitis Rats

Abstract: Gastroesophageal reflux disease (GERD) is induced by the reflux of stomach contents or gastric acid, pepsin into the esophagus for prolonged periods of time due to defection of the lower esophageal sphincter. Reflux esophagitis is a disease found in less than 50% of GERD patients. This study is aimed at evaluating the protective effect of Curcumae longae Rhizoma 30% EtOH extract (CLR) in acute reflux esophagitis (ARE) rats. CLR measured antioxidant activity through in vitro experiments. Based on the results, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In the study, we identified the downregulation of claudin-5 expression in damaged esophageal mucosal, while the expression of claudin-5 was increased by treatments of the ESE and ranitidine. Reflux esophagitis reportedly correlates with changes in the level of tight junction and inflammatory proteins, such as claudin, COX-2 and TNF-α (Nan, 2018;Hatware, 2018;Nam, 2019;Tetreault, 2016, Roh, 2021. In this study, the increase in COX-2 and TNF-α levels was confirmed in the reflux esophagitis model, and a significant decrease in inflammatory cytokine and protein was observed in the group treated with the ESE 100 mg/kg and the ranitidine group.…”
Section: Discussionsupporting
confidence: 63%
“…In the study, we identified the downregulation of claudin-5 expression in damaged esophageal mucosal, while the expression of claudin-5 was increased by treatments of the ESE and ranitidine. Reflux esophagitis reportedly correlates with changes in the level of tight junction and inflammatory proteins, such as claudin, COX-2 and TNF-α (Nan, 2018;Hatware, 2018;Nam, 2019;Tetreault, 2016, Roh, 2021. In this study, the increase in COX-2 and TNF-α levels was confirmed in the reflux esophagitis model, and a significant decrease in inflammatory cytokine and protein was observed in the group treated with the ESE 100 mg/kg and the ranitidine group.…”
Section: Discussionsupporting
confidence: 63%
“…The protein levels of the groups are expressed relative to those of the normal rat (represented as 1). We followed the methods of Lee et al [26].…”
Section: Preparation Of Nuclear and Cytosolmentioning
confidence: 99%
“…Band densities were measured using ATTO Densitograph Software (ATTO Corporation, Tokyo, Japan) and quantified as the ratio to histone or β -actin. The protein levels of the groups are expressed relative to those of the normal rat (represented as 1) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%